Locating the Bhagavadgita on the Deep Ecology Platform: A Study of Convergence and Divergence (KEMANUSIAAN The Asian Journal of Humanities, 2025)
Hinduism records a strong ecological underpinning in the dharmic system of life which is reflected in the core religious texts like the Bhagavadgita. In the text, the Brahman figure Krishna reveals himself as personified cosmic energy pervading all living and non-living beings and beyond. The eight-pointed deep ecology platform formulated by Arne Naess, demands a radical paradigm shift in human lifestyle for flourishing of nature and biodiversity and the ecosophy conceptualises individual eco-consciousness. As deep ecology was influenced by the Bhagavadgita also, the present study investigates the converging and diverging relations between the deep ecology and the Bhagavadgita and, thereby, foregrounding the limitations of the former to unravel the ecological discourse of the text.